Pembangunan Aplikasi Mobile Kontributor untuk Pengisian Informasi Publikasi dengan Model Agile - Fuad Lutfi; Budi Santoso; Baginda Oloan Lubis (Jurnal Teknologi Informatika dan Komputer, 2022)
The Pancasila Idealism Development Agency is a body that is under and responsible to the President, determines the policy direction for the development of Pancasila idealism, and assists, harmonizes, and advances Pancasila idealism. Carry out standardization, prepare education and training, organize education and training in a comprehensive and sustainable manner, and develop research results on policies or regulations that are not in accordance with Pancasila, ministries/agencies, and local governments. Socio-political organizations and other parts of society. The problem faced by the Pancasila Ideology Development Agency, especially at the Data and Information Center, is the need for an application that can provide convenience for contributors in filling out activity information on the Pancasila Idealism Development Agency website along with integration between mobile applications and websites. Based on the problems obtained, the researcher formulates the problem of how to design a mobile application that is able to accommodate existing business processes quickly and accurately, as well as make system documentation and report generation as a leader with a mobile application. The system development used in this study uses the Agile model.